Technology integration skills, technostress, and self-efficacy of selected public elementary teachers in District III of Batangas city - Bejasa, Eloisa F; Yango, Antonio R (Technium Education and Humanities, 2023)
The learning preference of students nowadays has changed due to technology. According to Hartman et al (2019), students no longer prefer the passive dissemination of information being delivered by a teacher. Yango et al. (2019) posit that studies show the introduction of the computer and the use of information and communications technology (ICT) in interpersonal interactions have altered how people interact with one another. Hence, teachers must be skillful enough to integrate technology into the learning process. Akram et al .(2022) revealed in their study that teachers have favorable opinions of the use of technology in teaching and learning procedures. They believe that incorporating technology into their lessons helps them improve their teaching strategies, make learning engaging and interactive, and keep students motivated. However, Dong et al. (2019) posit that teachers are under pressure to keep up with new technologies and to develop pedagogical usage of technologies due to the rapid development of technologies and the gradually increasing requirements for technology integration into teaching. Technostress is understood to be the adverse psychological reaction to the stress that results from using technology (Llorens as cited in Penado et al, 2021). According to studies, using technology in the classroom not only improves learning but also has a negative impact on both the self-efficacy of teachers and their satisfaction with their jobs (Lee & Lim, 2020). This study determined the respondents’ technology integration skills; level of technostress in terms of techno-overload, techno-invasion, and techno- complexity; level of teachers’ self-efficacy; and the relationship between respondents’ level of technology integration skills and level of technostress; between respondents’ level of technology skills and level of self-efficacy; between the respondents’ level of technostress and level of self-efficacy; and how predictive are the level of technology integration skills and level of technostress taken singly or in combination, level of self-efficacy of teachers in public schools in Batangas City. The researcher utilized descriptive-correlational method of research with the help of survey questionnaire as the main source of data. Out of the total population of 153 teachers from District III in Batangas, 110 were selected as the respondents. Based on the findings, the following conclusions were drawn: the teachers’ level of technology integration skills is high; their level of technostress is low; the while their level of self -efficacy is high. Meanwhile, findings revealed that the higher the teachers’ level of technology integration skills, the higher their level of technostress; also the higher the level of teachers’ technology integration skills, the higher their level of self-efficacy, lastly the higher the teachers’ level of techno-invasion, the higher their level of self-efficacy. In addition, it was also found that the independent variables techno- overload and overall technostress are drivers of level of teacher self-efficacy among public elementary school teachers.